LITERATURE REVIEW THE EXISTENCE OF MARKETING PRODUCTS - Hafidz Hanafiah (International Journal of Multidisciplinary Research and Literature, 2023)
Marketing is part of management science that studies the activities of marketing products or services starting from planning, managing, implementing, controlling, to evaluating processes to meet the needs of the objectives of a particular company organization. One of them is the 4P marketing concept, namely Product, Pricing, Promotion, and Place. Product is one of the marketing concepts, something goods or services that can be bought and sold. Something that is complex, visible or invisible, in which there are price packages, company prestige and company services received by buyers to satisfy their wants and needs. In this study the aim was to find out the literature review of product existence from various journals and then synthesize it with a qualitative literature study. The results of the study show that a prolonged product existence is needed to retain customers both with innovation and technology; legality, strategy, and product factors; differentiation and branding; standardization; as well as marketing strategy.